THE INTERIOR DESIGN STUDY OF A LACTATION ROOM AT REGIONAL HOSPITALS OF SURAKARTA INDONESIA FROM THE PERSPECTIVE OF ERGONOMICS AND REGULATORY STANDARDS - Siti Badriyah; I Nyoman Suyasa (Institut Seni Indonesia Surakarta, 2020)
A lactation room is a vital facility used to support the smooth running of activities in public spaces for women, especially for nursing mothers. The lactation room is usually used by mothers to breastfeed their children privately in public spaces. This study aims to determine the ergonomics and standards of lactation rooms in public facilities in Surakarta-Indonesia. This study was used to determine whether nursing mothers experience difficulties, easiness, or convenience when using these facilities. Ergonomic measurement is essential to see whether the object follows the users' dimensions, especially mothers and their babies. The object of this research is the lactation rooms located in several general hospitals in Surakarta. The method used is descriptive with a qualitative approach supported by quantitative data, or in other words, a dual research strategy, which is the use of multiple methods in solving a research problem. The quantitative here use numerical data, which results from field measurements, then compared with referred references, resource persons, and analyzed based on the researchers' interpretation. This research's results were in lactation rooms in terms of ergonomics/anthropometry and lactation room standards. Moreover, this also serves as an input to stakeholders to provide good public facilities following ergonomic lactation rooms to function optimally. These beginner research results are also expected to enrich learning sources related to Ergonomics, Interior Design, and Furniture in Interior Design Study Program ISI Surakarta.